HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP PEMBERIAN IMUNISASI LENGKAP PADA BAYI DI DESA GUNUNG TUNYANG KECAMATAN TIMANG GAJAH - Ika Ulandari; Andi Pratama Putra; Raodah; Rahmah (Aceh Health Sciences Journal, 2026)
This study aimed to determine the relationship between parental knowledge and family support with the provision of complete basic immunization for infants in Gunung Tunyang Village, Timang Gajah Subdistrict. The research employed an analytical survey with a cross-sectional approach. The population consisted of 34 mothers with infants aged 0–24 months, selected using total sampling. Data collection instruments included questionnaires on knowledge, family support, and observation of immunization status from posyandu records. Data were analyzed using the Chi-Square test at a 95% confidence level. Results showed that most infants did not receive complete basic immunization (63.6%). A majority of respondents had low knowledge (53.0%) and insufficient family support (54.5%). Statistical tests revealed a significant relationship between knowledge and complete immunization (p=0.003), as well as between family support and complete immunization (p<0.05). The study concludes that parental knowledge and family support play crucial roles in improving immunization coverage. It recommends enhancing health education and family involvement to support immunization programs. Keywords: Family Support, Immunization, Knowledge